2015
DOI: 10.1016/j.jcrs.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Transscleral suture fixation following recurrent toric intraocular lens rotation

Abstract: We describe a surgical technique of transscleral suture fixation for recurrent rotation of a double-loop hydrophilic acrylic toric intraocular lens (IOL) in the capsular bag. Two 9-0 polypropylene sutures are placed in the proximal and distal angulations of 1 of the IOL haptics through the capsular bag. The clockwise and counterclockwise traction provided by these sutures prevents rotation of the IOL in either direction. This technique can be used in cases of spontaneous postoperative IOL rotation to achieve s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…There are several reports of transscleral fixation using different types of toric IOLs in diverse situations. [6][7][8][9] They all suggested that good stabilization and visual rehabilitation can be achieved through transscleral fixation of the IOLs. In this case, the haptic was temporarily externalized through a small clear corneal incision.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of transscleral fixation using different types of toric IOLs in diverse situations. [6][7][8][9] They all suggested that good stabilization and visual rehabilitation can be achieved through transscleral fixation of the IOLs. In this case, the haptic was temporarily externalized through a small clear corneal incision.…”
Section: Discussionmentioning
confidence: 99%
“…Sutured sulcus scleral fixation of Toric IOLs are already reported as treatment for dislocated in-the-capsular-beg lens [7][8][9] as well as for recurrent intraocular lens rotation 10 ; however, the long-term stability of this technique remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A straight and curved needle with 10-0 polypropylene suture (Ethicon, Inc.) was passed through a paracentesis into the barrel of the 26-gauge needle using a docking technique. 5 The needle was then retracted out of the eye. If necessary, one limbal conjunctival incision was created for perfusion of the balanced salt solution into the anterior chamber (AC).…”
Section: Methodsmentioning
confidence: 99%